THE IMPACT OF ONLINE GAMES ON SLEEP QUALITY IN SCHOOL AGE CHILDREN - Ana Zakiyyah; Roza Indra Yeni (Universitas Kadiri, 2025)
Excessive use of online games can have a negative impact on individual behavio, one of wich is reducing rest time and decreasing sleep quality, especially in school-age children. This research aims to determine the impact of online games on sleep quality in school-age children at SDN 11 Duri Kepa, West Jakarta. This research uses quantitative methods with a cross sectional approach. The total sample of 69 respondents was taken using a non-probability sampling method. Online game use was measured using the Game Addiction Scale for Adolescents and sleep quality was measured using the Pittsburgh Sleep quality Index. Meanwhile, the statistical test used is the chi-square test. Shows that more than half of the respondents use online games moderately, namely 47 respondents (68.1%). More than half of the respondents experienced poor sleep quality, namely 43 respondents (62.3%). The results of statistical tests show that there is a relationship between the use of online games and sleep quality in school-aged children with a p value = 0.001 (<0.05). The conclusion of this research is that there is a relationship between the use of online games and sleep quality in school-age children at SDN 11 Duri Kepa, West Jakarta. This research can be used as a source of information regarding the impact of online games on sleep quality in school-age children.